Spatio-temporal change monitoring for surface water on the Qinghai-Tibet Plateau from 1990 to 2020 using remote sensing - Sui, Tianbo; Ye, Chengming; Tang, Rong; Wei, Ruilong (Frontiers in Earth Science, 2023)
Detecting and analyzing changes of water resources is critical for human survival and societal development in the Qinghai Tibet Plateau (QTP). We implemented the cosine similarity method to complete the migration of samples and achieve a more accurate random forest classifier (mean Kappa = 0.872) for each period. Based on these classifiers and 45,370 Landsat images, we estimated the surface water distribution of the QTP for six periods between 1990 and 2020 based on the Google Earth Engine platform. The results indicate that the QTP has a surface water area of 57,229 ± 3,248 km2 (1990–1995), 58,444 ± 3,248 km2 (1996–2000), 67,319 ± 3,704 km2 (2001–2005), 67,399 ± 2,798 km2 (2006–2010), 70,286 ± 3,033 km2 (2011–2015), 75,176 ± 2,785 km2 (2016–2020), that the area of water rose by ap-proximately 31.3% and continued to increase. The area of permanent water remained constant between 1990 and 2020 at 47,280 km2. On the QTP, the change in water area can be split into four regions: rapid increase (Qiangtang Plateau), slow increase (eastern basins), decrease (northern and northeastern basins), and relatively stable (southern basins). About 186,408 km2 area of land is significantly losing water bodies, while about 589,567 km2 area of land is significantly gaining water bodies. This study provides higher accuracy temporal distribution data of water bodies in the Qinghai-Tibet Plateau, and quantitatively evaluates the area changes of water bodies from multiple spatial scales. Research provides an important scientific reference for hydrological research and effective management of water resources in important rivers in the QTP.